2018
DOI: 10.1111/php.13002
|View full text |Cite
|
Sign up to set email alerts
|

Nanolipid Formulations of Benzoporphyrin Derivative: Exploring the Dependence of Nanoconstruct Photophysics and Photochemistry on Their Therapeutic Index in Ovarian Cancer Cells

Abstract: With the rapidly emerging designs and applications of light-activated, photodynamic therapy (PDT)-based nanoconstructs, photonanomedicines (PNMs), an unmet need exists to establish whether conventional methods of photochemical and photophysical characterization of photosensitizers are relevant for evaluating new PNMs in order to intelligently guide their design. As a model system, we build on the clinical formulation of benzoporphyrin derivative (BPD), Visudyne , by developing a panel of nanolipid formulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(88 citation statements)
references
References 58 publications
2
85
1
Order By: Relevance
“…The PS, being conjugated to a nonswitchable phospholipid, remains anchored to the liposome during this process and eventually ends up trapped in lysosomes, thereby modulating (and expanding) the subcellular localization of BPD. Our prior work has demonstrated that this BPD anchoring behavior is unique from BPD formulated in the clinical preparation Visudyne, whereby the PS rapidly leaches out of the formulation in the presence of serum‐containing media . The rapid dissociation of BPD from Visudyne is therefore responsible for the mitochondria/ER subcellular localization, as is typical of native BPD.…”
Section: Discussionmentioning
confidence: 96%
“…The PS, being conjugated to a nonswitchable phospholipid, remains anchored to the liposome during this process and eventually ends up trapped in lysosomes, thereby modulating (and expanding) the subcellular localization of BPD. Our prior work has demonstrated that this BPD anchoring behavior is unique from BPD formulated in the clinical preparation Visudyne, whereby the PS rapidly leaches out of the formulation in the presence of serum‐containing media . The rapid dissociation of BPD from Visudyne is therefore responsible for the mitochondria/ER subcellular localization, as is typical of native BPD.…”
Section: Discussionmentioning
confidence: 96%
“…Depending on the type of photodamage and the underlying biology of the target cells, PDT can also cause lethal levels of autophagy , or as has been reported more recently, can trigger paraptosis, a response, in part, to misfolded endoplasmic reticulum (ER) proteins . Combining PS or PS formulations to enhance PDT efficacy by targeting complementary tumor compartments or subcellular sites has also shown promise . Importantly, because the timing, location and intensity of light activation can be carefully controlled, PDT is inherently a targeted therapeutic modality.…”
Section: Targeting the Tumor Microenvironment With Photochemistrymentioning
confidence: 99%
“…The photosensitiser Benzoporphyrin Derivative (BpD) has been the subject of many previous PDT investigations, gaining FDA approval in 2000 for clinical applications [79]. Huang et al found a liposomal formulation of BpD to be an efficient mediator of PDT in MIA PaCa-2 pancreatic cancer cells [80].…”
Section: Benzoporphyrin Derivativementioning
confidence: 99%